Plants vs. zombies. 11, War and peas - Tobin, Paul, 1965- (Plants vs. zombies (Milwaukie, Or.), 2018)
The position of leader of the book club opens up, and the plants versus zombies rivalry heats up as Zomboss and Crazy Dave compete for the position while Nate, Patrice, and their plants join a scholarly scuffle.